ABCC10 Plays a Significant Role in the Transport of Gefitinib and Contributes to Acquired Resistance to Gefitinib in NSCLC - Zhao, Hongbo; Huang, Yutang; Shi, Jingjing; Dai, Yi; Wu, Lanxiang; Zhou, Honghao (Frontiers in Pharmacology, 2018)
Gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), is used clinically as first-line therapy in patients with advanced non-small cell lung cancer (NSCLC) with EGFR activating mutations, but the inevitable development of acquired resistance limits its efficacy. In up to 30-40% of NSCLC cases, the mechanism underlying acquired resistance remains unknown. ATP-binding cassette (ABC) transporters are a family of membrane proteins that can significantly influence the bioavailability of numerous drugs, and have confirmed to play an essential role in multidrug resistance (MDR) in cancer chemotherapy. However, their role in acquired resistance to gefitnib in NSCLC has not been well studied. Here, through RNA sequencing (RNA-Seq) technology we assessed the differentially expressed ABC transporters in gefitinib-sensitive (PC9 and H292) and gefitinib-resistant (PC9/GR and H292/GR) NSCLC cells, with ABCC10 identified as a transporter of interest. Both ABCC10 mRNA and protein were significantly increased in acquired gefitinib-resistant NSCLC cells, independent of EGFR mutation status. In vitro transport assay showed that ABCC10 could actively efflux gefitinib, with an efflux ratio (ER) of 7.8. Further results from in vitro cell line models and in vivo xenograft models showed that overexpression of ABCC10 led to a reduction in gefitinib sensitivity through decreasing the intracellular gefitinib accumulation. Our data suggest that ABCC10 has an important role in acquired resistance to gefitinib in NSCLC, which can serve as a novel predictive marker and a potential therapeutic target in gefitinib treatment.